2021
DOI: 10.3390/biomedicines9121899
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative Stress Molecules in Multiple Sclerosis: A Meta-Analysis

Abstract: Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system of unknown etiology. As it is still a diagnosis of exclusion, there is an urgent need for biomarkers supporting its diagnosis. Increasing evidence suggests that nitrosative stress may play a pivotal role in the pathogenesis of MS. However, previous reports supporting the role of nitrosative stress molecules as disease biomarkers are inconsistent overall. We therefore systematically analyzed the existing literature to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Nevertheless, in contrast to the serum, CSF NOx levels did not significantly differ between RRMS and Soma patients, indicating that the diagnostic value of NOx is more pronounced in the serum than in the CSF. Notably, even though the investigated groups are only partly comparable, this is a not in line with the results of our meta-analysis [10]. Pathophysiologically, however, this might simply point to the pivotal contribution of the peripheral immune system to the inflammatory processes in MS. On the other hand, we found a positive correlation between the EDSS and overall CSF NOx levels.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Nevertheless, in contrast to the serum, CSF NOx levels did not significantly differ between RRMS and Soma patients, indicating that the diagnostic value of NOx is more pronounced in the serum than in the CSF. Notably, even though the investigated groups are only partly comparable, this is a not in line with the results of our meta-analysis [10]. Pathophysiologically, however, this might simply point to the pivotal contribution of the peripheral immune system to the inflammatory processes in MS. On the other hand, we found a positive correlation between the EDSS and overall CSF NOx levels.…”
Section: Discussionsupporting
confidence: 79%
“…Our previous meta-analysis found significantly increased CSF NOx levels in RRMS patients compared to NIOND [10]. We therefore measured CSF NOx levels in 26 RRMS compared to 12 Soma patients, but did not find significant differences between the two groups (Figure 2A).…”
Section: No Relevant Differences In Csf Nox Levels Between Rrms and S...mentioning
confidence: 80%
See 2 more Smart Citations
“…amyotrophic lateral sclerosis, Alzheimer's disease, Parkinson's disease and Huntington's disease) Inflammation and neurodegeneration are mutually dependent phenomena [18]. The cause of multiple sclerosis (MS) remains a mystery [19]. Several studies have shown that tiny, oxygen-derived molecules called reactive oxygen species (ROS) may have a role in the pathophysiology of multiple sclerosis [1].…”
Section: Discussionmentioning
confidence: 99%